Determinant of MSMEs Financial Management Behavior in Yogyakarta City - Khairi, Afiq; Muhfiatun (Universitas Islam Negeri Raden Intan, 2025)
This study aims to determine whether locus of control, Islamic financial literacy, and demographic factors affect financial management behavior in MSMEs aimed at MSMEs registered at the Yogyakarta city cooperative and SME industry office, and as many as 140 MSME players were used as objects in this study. This study uses primary data by distributing questionnaires offline and online to MSME and SME actors. The hypothesis proposed was statistically tested using Multiple Linear Regression Analysis techniques, while the software used SPSS 27 and Microsoft Excel. The results showed that the variables of locus of control and Sharia financial literacy had a significant positive effect on financial management behavior in Yogyakarta city MSMEs, while the demographic factor variable had no effect on financial management behavior in Yogyakarta city MSMEs. Keywords: MSMEs, locus of control, Sharia Financial Literacy, Demographic Factors